Hepatic R2* is more strongly associated with proton density fat fraction than histologic liver iron scores in patients with nonalcoholic fatty liver disease. Issue 5 (14th October 2018) - Bashir, Mustafa R.; Wolfson, Tanya; Gamst, Anthony C.; Fowler, Kathryn J.; Ohliger, Michael; Shah, Shetal N.; Alazraki, Adina; Trout, Andrew T.; Behling, Cynthia; Allende, Daniela S.; Loomba, Rohit; Sanyal, Arun; et al.
Abstract : Background: The liver R2* value is widely used as a measure of liver iron but may be confounded by the presence of hepatic steatosis and other covariates. Purpose: To identify the most influential covariates for liver R2* values in patients with nonalcoholic fatty liver disease (NAFLD). Study Type: Retrospective analysis of prospectively acquired data. Population: Baseline data from 204 subjects enrolled in NAFLD/NASH (nonalcoholic steatohepatitis) treatment trials. Field Strength: 1.5T and 3T; chemical‐shift encoded multiecho gradient echo. Assessment: Correlation between liver proton density fat fraction and R2*; assessment for demographic, metabolic, laboratory, MRI‐derived, and histological covariates of liver R2*. Statistical Tests: Pearson's and Spearman's correlations; univariate analysis; gradient boosting machines (GBM) multivariable machine‐learning method. Results: Hepatic proton density fat fraction (PDFF) was the most strongly correlated covariate for R2* at both 1.5T ( r = 0.652, P < 0.0001) and at 3T ( r = 0.586, P < 0.0001). In the GBM analysis, hepatic PDFF was the most influential covariate for hepatic R2*, with relative influences (RIs) of 61.3% at 1.5T and 47.5% at 3T; less influential covariates had RIs of up to 11.5% at 1.5T and 16.7% at 3T. Nonhepatocellular iron was weakly associated with R2* at 3T only (RI 6.7%), and hepatocellular iron was not associated with R2* at either field strength. Data Conclusion: Hepatic PDFF is the most influential covariate for R2* at both 1.5T and 3T; nonhepatocellular iron deposition is weakly associated with liver R2* at 3T only. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1456–1466.